An Investigation of the Effect of Ionic Strength on Micellization Behaviors of a Cationic Surfactant - Basnet, Nabin; Shrestha, Prabesh; Neupane, Shova; Yadav, Amar Prasad; Bhattarai, Ajaya (Amrit Research Journal, 2025)
The conductivity measurement of tetradecyltrimethylammonium bromide (TTAB) provides information about its micellization behaviors in the presence of salts NaNO3 and Na2SO4 in aqueous solutions. The presence of NaNO3 and Na2SO4 in aqueous solutions of TTAB greatly influences the critical micellization concentration (CMC) of TTAB at 298.15, 308.15, and 318.15 K temperatures. Precisely measured conductivity data were used to determine CMC, degree of counter-ion dissociation (a), free energy of micellization (DGm°), enthalpy of micellization (DHm°), and entropy of micellization (DSm°) of the TTAB in aqueous solutions in the presence of inorganic salts. The ionic strength in solution due to the presence of NaNO3 and Na2SO4 affects the micellization thermodynamics of the TTAB in salt-water solvent systems. The study provides valuable insights regarding the effect of ionic strength, hydrophobic interaction, enthalpy change, and entropy change on micellization behaviors of TTAB. The DGm°and DHm°of TTAB becomes more negative in the presence of both NaNO3 and Na2SO4 in aqueous solution, whereas DSm° found to be maximum in the presence of Na2SO4. An increase in temperature in the investigated range increases the CMC of the TTAB in salt-water solvent systems.